Blood-Based Inflammatory Biomarkers: A Literature Review - Zahara Nurfatihah Z; Ghea Farmaning Thias Putri; Elsa Septiani Putri (CV. Wadah Publikasi Cendekia, 2026)
Introduction: Inflammation is a fundamental biological response involved in the development and progression of various diseases and is commonly assessed using indicators detected in blood. A wide range of inflammatory biomarkers has been described. However, differences in their biological characteristics and clinical relevance require clear understanding for appropriate use. Objective: This review aims to summarize the blood-based inflammatory biomarkers and to present a clear description of their characteristics, strengths, and limitations, as well as key concepts related to their clinical application and interpretation as indicators of inflammatory activity. Method: This study was conducted as a literature review using secondary data from scientific publications. Articles published within the last five years were identified from PubMed, Scopus, and Google Scholar and selected based on their relevance to blood-based inflammatory biomarkers and the clarity of reported information. The selected literature, consisting of original research articles and review papers, was analyzed descriptively to synthesize and compare findings across studies. Result: The results indicate that blood-based inflammatory biomarkers can be grouped into several main categories, each reflecting different mechanisms and stages of inflammation. Differences in biological function and applicability were observed among biomarker groups, highlighting variations in their usefulness depending on inflammatory context. Conclusion: Blood-based inflammatory biomarkers provide important information for evaluating inflammatory status. Accurate assessment depends on interpretation that accounts for biological function, inflammatory context, and inherent limitations of each biomarker.